Africans in post-COVID-19 pandemic China: is there a future for China's 'new minority'?. Issue 4 (1st October 2020) - Castillo, Roberto; Amoah, Padmore Adusei
ABSTRACT: In this article, we reflect on critical questions relating to the future of African migration to China in the post-COVID-19 world at the backdrop of the mistreatment many Africans received as part of the pandemic control in China. These questions include: Is this the end of African migration to China as we know it? Will COVID-19 fundamentally change how we think about migration, mobility and wellbeing in the People's Republic of China (PRC)? What will be the effect of the post-COVID-19 regime on the social identity and wellbeing of the African diaspora in Guangzhou and other Chinese cities?